An overview of the biologic effects of omega-6 oxylipins in humans. (October 2018) - Shearer, Gregory C.; Walker, Rachel E.
Highlights: n6 oxylipins have use in predicting risk, particularly for cardiovascular disease. Esterified n6 oxylipins appear to be more sensitive to dietary and pharmaceutical interventions, particularly among HDL, LDL, and VLDL. Numerous n6 oxylipins have activities that complement n3 oxylipins. In some cases, n6 oxylipins have activities that counter-act detrimental activities of n3 oxylipins. Abstract: Oxylipins are lipid mediators produced from polyunsaturated fatty acid (PUFA) metabolism, and are thought to be a molecular explanation for the diverse biological effects of PUFAs. Like PUFAs, oxylipins are distinguished by their omega-6 (n6) or omega-3 (n3) chemistry. We review the use of n6 oxylipins as biomarkers of disease and their use in diagnosis and risk assessment. We show cases where oxylipins derived from linoleate (LA) or arachidonate (AA) produced by the activities of lipoxygenase, cyclooxygenase, epoxygenase, ω/ω-1 hydroxylase, and autooxidation are useful as biomarkers or risk markers. HODEs, KODEs, EpOMEs, DiHOMEs, and other metabolites of LA as well as prostanoids, HETEs, KETEs, EpETrEs, and DiHETrEs, and other metabolites of AA were useful for understanding the different signaling environments in conditions from traumatic brain injury, to major coronary events, dyslipidemia, sepsis, and more. We next evaluate interventions that alter the concentrations of n6 oxylipins in plasma. We note the utility and response of each plasma fraction, and the generally increasing utility from the non-esterified, to the esterified, to the lipoprotein fractions. Finally, we review the effects which are specifically related to n6 oxylipins and most likely to be beneficial. Both n6 and n3 oxylipins work together in an exceedingly complex matrix to produce physiological effects. This overview should provide future investigators with important perspectives for the emerging utility of n6 oxylipins as products of n6 PUFAs in human health.